World integration tendencies in the higher education sphere - Konopyanova, G.; Baikenov, Zh.; Brauweiler, H.-Ch. (BUKETOV BUSINESS REVIEW, 2018)
Current trends in the development of higher education institutions, diversification of university activities make the development of international cooperation contribute to the advantages and survival of the university in the time of tough competition in the education market increasingly important. International cooperation can be realized both via the integration of universities and study programs. The latter often takes the form of academic mobility of students and teachers with the goal of broadening their worldview and acquiring international experience in higher education. The article gives an analytical survey of student academic mobility in different countries and the change in the student academic mobility map. The public policy of some countries has brought about changes in the choice of the countries students make when deciding where to study. An analysis of academic mobility of students from post-Soviet countries has revealed that the greater number of students, who go to study abroad than that of international students who come on the international mobility programs, results in imbalance in academic mobility. The article gives an analytical survey of student academic mobility with the conclusion that at present the integration process tends to focus on mobility only, though integration has much more implications.